THE ROLE OF POLITICIANS, SCIENTISTS AND MEDIA IN THE LITHUANIAN ENERG Y SECURITY DISCOURSE - Genys, Dainius (Sociologija. Mintis ir veiksmas, 2015)
This article makes use of discourse analysis to examine the interrelation of politics, science and media in the Lithuanian discourse on energy security. It argues that, considered as a discursive formation in Foucault’s terms , this energy security discourse is still in the early stages of its development: within it, politicians, scientists and media commentators have different arguments, orientations, procedures, terminologies and finally goals. There is for example no clear rational framework for using scientific arguments in the context of politics. It is also unclear how the media can serve as a substantive watchdog over government policy towards energy. Further, scientific writing noticeably lacks communicative efficacy, the effect being to restrict the potential of scientific discourse in helping politicians make more sustainable decisions, and in helping media commentators to ground their arguments on a more solid and scientific basis. All of this leads to a rather spontaneous and elementary discursive formation, one which does not permit the realisation of more consistent and complete state policies towards energy security.
Keywords: politics; science; media; CDA; discourse; energy security